THE SCHOOL SPORT BY USING CAPITAL'S THEORY OF PIERRE BOURDIEU (Fiep Bulletin - online, 2015)
The present study analyzed the sport in educational institutions, by using  theoretical presuppositions of the French sociologist Pierre Bourdieu. The used methodological procedures were of qualitative nature. Teachers and students of the junior teams were interviewed. They were winners of the school championship in the city of São Paulo, in the year of 2001. The interviews were analyzed and discussed starting from the point of view of Bourdieu's analytical categories from Bourdieu, what resulted in the identification of fights inside the field and of disparities caused by the different accumulations of capitals, indicating the presence of significant inequalities among the participants of the competition.
Keywords: culture; school sport; habitus; capital's Theory.